THE RESULT OF THE SURGICAL TREATMENT OF INTRADURAL-EXTRAMEDULLARY SCHWANNOMA (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Schwannomas are the most common intradural extramedullary tumors of the spine, which observed at any age, more often in women and they can occur on any nerve of the human body. They usually occupy a posterolateral or lateral position in relation to the cord. The ventral midline is a very rare location for the origin of a spinal schwannoma [1]. Intradural intramedullary lesions comprise 20 to 30% of all primary spinal cord tumors [2]. The remaining 70 to 80% of primary intradural tumors are intradural extramedullary tumors [3]. Since their ventral location inhibits tumor visualization, the surgical removal of these lesions may result in spinal cord injury. Consequently, different surgical approaches have been suggested [4].